Impact of Open Dumpsites on Groundwater Quality: Geophysical and Hydrochemical Evidence from Ijan-Ekiti, Nigeria - Raphina O. UBAH; Oluwaseun S. OGUNGBEMI; Olabode O. OLUTOMILOLA (FUDMA Journal of Engineering and Technology, 2026)
Rapid urbanization and poor waste management practices in many developing regions have increased the risk of groundwater contamination from open dumpsites. This study investigates the impact of leachate migration from the Ikota Street dumpsite in Ijan-Ekiti, southwestern Nigeria, using an integrated geophysical and hydrochemical approach. Audio-magnetotelluric (ADMT) surveys were conducted along two traverses to delineate subsurface resistivity structures, while water samples from a hand-dug well and a nearby stream were analyzed for physicochemical parameters and heavy metal concentrations. Geophysical results reveal a heterogeneous subsurface characterized by high-resistivity zones in the near surface, underlain by low-resistivity anomalies interpreted as leachate plumes. These plumes occur at depths between approximately −70 m and −190 m and exhibit both vertical and lateral migration through preferential pathways such as fractures and permeable layers. A deep, highly conductive zone identified between −250 m and −310 m suggests the presence of a groundwater reservoir potentially impacted by leachate infiltration. Physicochemical analysis indicates that general water quality parameters, including pH and total dissolved solids, fall within limits recommended by the World Health Organization. However, elevated concentrations of toxic trace metals, particularly arsenic (0.015 mg/L) and cadmium (0.004 mg/L) in stream water, exceed permissible limits, indicating contamination. The presence of lead, cadmium, and arsenic in both water sources confirms leachate influence and highlights potential risks of bioaccumulation and long-term health effects. Generally, the study demonstrates that the dumpsite is actively contributing to groundwater and surface water contamination. The findings underscore the vulnerability of fractured basement aquifers to pollution and emphasize the need for improved waste management and groundwater protection strategies.